Biometria de sementes de maracuja selvagem (passiflora foetida l.) - Sousa, Wanielson Max de (Universidade Federal Rural do Semi-Árido, 2019)
BIOMETRY OF WILD PASSION SEED (Passiflora foetida): The objective of this work was to evaluate the biometrics of Passiflora foetida rootstock of wild passion fruit. The seeds were collected in an experimental area of the campus of the Federal Rural University of Semi-Arid (UFERSA), located in Mossoró, RN, following to the phytotechnic laboratory to determine the following characteristics: length, width, thickness and weight of the seeds. seeds. Descriptive and graphical analyzes were performed using the R-version 3.1.1 statistical software package. (2018). The variables length, width, thickness and weight presented high amplitude of variation, except for the length / width ratio which presented low amplitude of variation. There was a regular degree of symmetry for frequency distributions of length, width, length / width ratio, thickness and seed weight. It was also found the significant positive simple linear correlation between length and width, length and thickness, width and length / width ratio, width and thickness and length / width and thickness ratio, and that data for all seed characteristics Passiflora foetida evaluated in this study fit the normal probability distribution, which allowed the calculation of Pearson's simple linear correlation coefficient.
Monografia
Keywords: Fruticultura; Distribuição de Frequências; Estatística; Fruit Farming; Frequency Distribution; Statistics; CIENCIAS AGRARIAS::AGRONOMIA